At least three distinct proteins are necessary for the reconstitution of a specific multiprotein complex at a eukaryotic chromosomal origin of replication. - Estes, H G (1992)
We have reconstituted in vitro a multistage assembly of a protein complex that specifically recognizes a yeast genomic origin of replication, the autonomously replicating sequence ARS121. The first step in the assembly was the interaction of the known origin-binding factor OBF1 and another factor, OBF2, with the ARS121 origin of replication to form the OBF1-OBF2-origin complex. This complex was the substrate for the ATP-dependent binding of a third DNA-binding activity, the core binding factor, CBF. Binding of CBF to the origin, identified by the retarded mobility of the origin DNA fragment in agarose gels, required, in addition to ATP and the OBF1-OBF2-origin complex, a functional essential core nucleotide sequence. ARS121 DNA containing mutations in the core, which inactivate the origin in vivo, did not sustain stable CBF binding, whereas ARS121 DNA mutated outside the boundaries of the essential core, which has normal origin function, bound CBF as wild type. This tight, direct correlation between the ability of the origin to bind CBF and its function as an origin of replication in vivo strongly suggest that the multiprotein complex reconstituted in vitro has a key role in the initiation of DNA replication.